Effect of work from home which impacted on turnover intention during covid-19 pandemic - Paulus Sugiarto; Ferryal Abadi (Institute of Computer Science (IOCS), 2023)
The implementation of the Work From Home (WFH) policy is believed to be able to suppress the growth rate of COVID-19 cases, so this policy was enacted to slow the spread of Covid-19 while preventing sustainable economic losses. This study aims to determine the relationship and analyze the effect of WFH on job satisfaction, organizational commitment, and work motivation that has an impact on turnover intention in the technological era during the Covid-19 pandemic. The respondents in this study were 207 respondents of employees working in start-up companies, especially technology-based companies in the Jabodetabek area on a local and national scale which were taken using the purposive sampling method. This research is quantitative and uses the PLS Structural Equation Model (SEM-PLS) analysis tool. The results of this study show that WFH has a positive and significant effect on job satisfaction, organizational commitment, and work motivation. Then job satisfaction and organizational commitment have a negative and insignificant effect on turnover intention but work motivation does not have a negative effect on turnover intention. This research contributes to increasing knowledge about the impact of WFH on employee behavior at work, and can be a consideration for companies to develop new strategies to create a good work environment.